Needs of parents in critically ill infants care in the Neonatal Intensive Care Unit (NICU) - Sri Hendrawati; Sari Fatimah; Siti Yuyun Rahayu Fitri; Ai Mardhiyah; Ikeu Nurhidayah (University of Muhammadiyah Malang, 2018)
Infants hospitalization in the neonatal intensive care unit adversely affect for infants and parents. Efforts that can be developed to minimize the negative impact is by applying family centered care. The first step is to identify needs of parents. In previous study examined the differences in needs of particular groups of parents. This study aimed to identify the needs of parents in critically ill infants care in the neonatal intensive care unit. The research method was descriptive quantitative design. The samples were 45 respondents and data collection was done by using questionnaires NICU Family Need Inventory. Data analysis was done by score mean. This research has been carried out in the NICU Government Hospital of Bandung Raya. The quantitative result indicated that parents with critically ill infants in the NICU need assurance most (M = 3,90), followed by information (M = 3,82), proximity (M = 3,76), support (M = 3,49), and comfort (M = 3,37). Needs of parents are focused on the wellbeing of their infants. In doing nursing care, in addition to improving care to the infants, the nurses also should pay attention to needs of parents related to the assurance that their infants get the best care, open communication, and close contact with their infants. By identifying the needs of parents in the NICU, it can allow nurses to integrate the needs of parents into family centered care so that parents can meet these needs, get satisfaction, and can improve the quality of life infants.